Flood hazard identification and mitigation in semi- and arid environments - French, Richard H.; Miller, Julianne J. (World Scientific Publishing, 2012)
Alluvial fans are ubiquitous geomorphological features that occur throughout the world, regardless of climate, at the front of mountains as the result of erosion and deposition. Thsi title summarizes the current state, from the viewpoint of engineering, in the identification and mitigation of flood hazard on alluvial fans.